Coxiella Endocarditis as the Cause of Recurrent Fever and Brain Abscess in a Patient with Complex Congenital Heart Disease: A Case Report and Literature Review. (24th June 2020) - Ziogas, Ioannis A.; Evangeliou, Alexandros P.; Tsachouridou, Olga; Arvanitaki, Alexandra; Tsona, Afroditi; Kamperidis, Vassilios; Papagianni, Marianthi; Panagiotidis, Theofilos; Tourtounis, Ilias A.; Giannakoulas, George; Metallidis, Symeon
Abstract : Introduction . Blood culture-negative infective endocarditis (BCNIE) can present subtly and is associated with a diagnostic delay leading to increased morbidity and mortality. Case Report . We present the case of an 18-year-old male with a history of complex congenital heart disease and 3-year intermittent episodes of fever of unknown origin, who was referred to our hospital for upper and lower extremity focal seizures. Laboratory blood tests were normal, blood cultures were negative, and brain imaging revealed an abscess. Cardiology consultation was requested, and transthoracic echocardiography revealed an intracardiac vegetation. Empiric antibiotic treatment with sultamicillin, gentamycin, and meropenem was initiated. Serology testing was positive for Coxiella burnetii, and the diagnosis of BCNIE was established. The antibiotic course was changed to oral doxycycline for 36 months and led to resolution of IE, with no vegetation detected on TTE after 15 months. Conclusion . BCNIE is a life-threatening disease entity that can lead to severe complications, such as valve regurgitation, emboli, and death. Patients with congenital heart disease are particularly vulnerable to IE. Timely diagnosis and antibiotic management are of paramount importance in order to avoid the potentially fatal sequelae.